THE DEVELOPMENT OF ASSISTED WORKSHEETS DIFFERENTIATION LEARNING BASED ON LEARNING STYLE: HOW GREAT IT CAN HELP STUDENTS’ MATHEMATICAL UNDERSTANDING ABILITY? - Cucun Sutinah; Muhammad Ghiyats Ristiana (Jurnal Cakrawala Pendas, 2023)
The purpose of this study is to develop mathematics differentiation learning worksheets based on learning style and to know the impact for mathematics understanding ability in 4th grade. The method we used was R&D including 10 steps. The instruments were a validation test, questionnaire for teachers and students, and an understanding concept test. Validation and questionnaire data analyzed by descriptive quantitative. Although, mathematics understanding ability data analyzed by difference test and N-Gain test. The results of this study show that the differentiation learning worksheets fit with the criteria. Eligibility validation from experts gets an average of 91%. Practically based on teachers and students’ responses get an average 86%. It means that the learning materials are very valid. The learning materials in experiment class can increase the understanding concept with N-Gain 0,74. We can conclude that with mathematics differentiation learning worksheets can increase mathematics understanding ability. Penelitian ini bertujuan untuk mengembangkan LKPD Matematika Berdiferensiasi Gaya Belajar dan mengetahui pengaruhnya terhadap kemampuan pemahaman matematis siswa di kelas IV SD. Metode yang digunakan adalah penelitian dan pengembangan (RnD) yang terdiri atas 10 langkah. Instrumen pengumpul data meliputi lembar validasi, angket respon guru dan siswa, dan tes pemahaman konsep. Data validasi dan kepraktisan dianalisis secara kuantitatif deskriptif, sedangkan data kemampuan pemahaman matematis dianalisis dengan uji beda dan n-gain. Hasil penelitian menunjukkan bahwa LKPD berdiferensiasi yang dikembangkan memenuhi kriteria kelayakan, kepraktisan, dan keefektifan. Validasi kelayakan oleh ahli memperoleh rata-rata skor 91% (sangat layak). Kepraktisan mengacu pada respon guru dan siswa memperoleh rata-rata skor 86% (sangat baik). LKPD berdiferensiasi di kelas eksperimen mampu meningkatkan kemampuan pemahaman matematis secara efektif dibanding kelas kontrol dengan n-gain 0,74. Berdasarkan hasil tersebut, dapat disimpulkan bahwa peningkatan kemampuan pemahaman matematis siswa sesuai gaya belajarnya dapat dipengaruhi oleh LKPD berdiferensiasi.